Metode Demonstrasi dalam Peningkatan Motivasi Belajar Tilawatil Qur’an - Ikhwan, Afiful; Ferry Irawan Febriansyah; Aldo Redho Syam; Heriadi (Tahta Media Group, 2022)
This research is motivated by a phenomenon of the lack of application of learning methods carried out. However, the demonstration method which is one of the best methods has received less attention and lack of development. This is marked by the number of people who in learning make noise, indifferent and busy themselves by not responding to what is taught by educators. The purpose of this study was to determine the application of the Qur'an Tilawatil learning demonstration method and to describe efforts to increase motivation to learn Tilawatil Qur'an, using a qualitative research method with a case study approach. The results of this study the mentoring team stated that efforts to increase motivation to learn tartilul qur'an with this demonstration method were based on the orientation to make learning effective, efficient and relevant to the community. Efforts to increase this motivation are generally carried out in two ways, first, through direct demonstrations both in the form of recordings and from direct educators, including through